Institutional Isomorphism And Adoption Of International Public Sector Accounting Standards By African Countries - Munir Manini , Dr. Muganda (International Journal of Scientific Research and Management (IJSRM), 2019)
The international harmonization of financial reporting standards in the public sector is one of the significant public sector accounting reforms which have gained prominence in the recent past under the New Public Financial Management order. However, previous empirical evidence provided mixed results on the extent of African countries’ decision on the adoption of International Public Sector Accounting Standards and its relationship with institutional isomorphism factors. The purpose of this study was to examine the influence of institutional isomorphism (normative, mimetic and coercive) on the adoption International Public Sector Accounting Standards by African countries. The target population was 54 countries; however the final sample was 29 countries which comprised the dataset. A logistic regression analysis was thereafter conducted. Based on the Institutional Theory, the study revealed external public funding (coercive isomorphic pressure), the countries’ global competitiveness (mimetic isomorphic pressure), and human capital (normative isomorphic pressure) were non significant factors in a countries decision to adopt IPSAS. This study contributes to the literature on the international accounting in the public sector. The results of the study have significant managerial and theoretical implications for accounting standards regulators, researchers, and multilateral organizations.